2018
DOI: 10.1634/theoncologist.2017-0398
|View full text |Cite
|
Sign up to set email alerts
|

Early and Locally Advanced Metaplastic Breast Cancer: Presentation and Survival by Receptor Status in Surveillance, Epidemiology, and End Results (SEER) 2010–2014

Abstract: This population-based study reports recent outcomes, by receptor status, for women with metaplastic breast cancer. Survival in metaplastic breast cancer is not impacted by hormone receptor status. To the authors' knowledge, this is the first report indicating that women with human epidermal growth receptor 2 (HER2) positive metaplastic breast cancer have survival superior to women with HER2 negative metaplastic breast cancer and survival similar to women with HER2 positive invasive ductal carcinoma. This infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 36 publications
(50 reference statements)
6
99
2
Order By: Relevance
“…In a multivariate analysis of the SEER data, Nelson et al [3] reported a significant association between reduced survival time and LN positivity, ER and PR negativity, high grade, and tumour size. Further, in an assessment of contemporarily treated MBC, HER2 status was shown to have a significant prognostic impact, implying a responsiveness to HER2-directed therapy [29]. In contrast, our cohort demonstrates the prognostic impact of tumour size; however, we do not see significant impacts on survival made by age at diagnosis, lymph node status, grade or lymphocytic infiltrate.…”
Section: Discussioncontrasting
confidence: 71%
“…In a multivariate analysis of the SEER data, Nelson et al [3] reported a significant association between reduced survival time and LN positivity, ER and PR negativity, high grade, and tumour size. Further, in an assessment of contemporarily treated MBC, HER2 status was shown to have a significant prognostic impact, implying a responsiveness to HER2-directed therapy [29]. In contrast, our cohort demonstrates the prognostic impact of tumour size; however, we do not see significant impacts on survival made by age at diagnosis, lymph node status, grade or lymphocytic infiltrate.…”
Section: Discussioncontrasting
confidence: 71%
“…Metaplastic breast carcinoma (MBC) is a rare breast cancer subtype, constituting w1% of all invasive breast cancers. 1 Histologically, MBC is a highly heterogeneous disease, encompassing 6 different morphologic subtypes, including spindle, squamous, chondroid, osseous, rhabdomyoid, and mixed morphology. 1 Somatic mutations in TP53, PI3K MAPK, RB1, and Wnt pathways genes have been frequently described in MBCs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Histologically, MBC is a highly heterogeneous disease, encompassing 6 different morphologic subtypes, including spindle, squamous, chondroid, osseous, rhabdomyoid, and mixed morphology. 1 Somatic mutations in TP53, PI3K MAPK, RB1, and Wnt pathways genes have been frequently described in MBCs. [2][3][4][5][6][7][8][9][10][11] MBCs are basallike and claudin-low breast cancers with a triple-negative phenotype: estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2/neu)-negative.…”
Section: Introductionmentioning
confidence: 99%
“…prove the outcome of LABC [21][22][23], better quality of life can be achieved with IBR. This is extremely significant for survivors of breast cancer.…”
mentioning
confidence: 97%